PELITA DHARMA: Keutamaan Dharma Menurut Sarasamuccaya - I Ketut Wisarja; Ni Wayan Aryani; Ni Nyoman Suastini (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2022)
Rapid progress in the field of information and technology on the one hand makes human life easier and pragmatic, but on the other hand it raises quite deep concerns because it has negative impacts, such as; triggers stress, irritability, self-determination, and selfishness. This article aims to discuss and analyze the virtues of dharma as a light or enlightenment of the spirituality of human life and its implementation for Hindus, with the aim of realizing a peaceful, peaceful, harmonious, and happy society both physically and mentally. Therefore, make dharma as a basis in seeking wealth, seeking satisfaction, obtaining happiness, and as a means to heaven. Practically, this article is expected to be useful for Hindus as a guide and foundation in carrying out all activities of daily life.